Secure and efficient token based roaming authentication scheme for space-earth integration network - Kaiping XUE; Yongjin MA; Jia’nan HONG; Jie XU; Qingyou YANG (Tongxin xuebao)
Aiming at the problem of prolongation and instability of satellite and terrestrial physical communication links in the space-earth integration network,a two-way token based roaming authentication scheme was proposed.The scheme used the characteristics of the computing capability of the satellite nodes in the network to advance the user authentication process from the network control center (NCC) to the access satellite.The satellite directly verified the token issued by the NCC to verify the user's identity.At the same time,the token mechanism based on the one-way accumulator achieved the user's dynamic join,lightweight user self-service customization and billing,and the introduction of Bloom Filter enabled effective user revocation and malicious access management.Compared with the existing scheme,the scheme can guarantee the security of roaming authentication and significantly reduce the calculation and communication overhead of the authentication and key negotiation process.